Urban Services Delivery and the Poor : The Case of Three Central American Cities, Volume 2. City Reports - World Bank (Washington, DC, 2013)
The present study describes, and quantifies the provision of basic urban services to the poor, in three Central American cities in El Salvador, Honduras, and, Panama. It also identifies priority areas for government intervention, using specialized household surveys to quantify current deficits, and to rank households from poor to rich, using aggregate consumption as the measure of welfare. The urban poverty profile is examined in each city, through migration, growth, and mobility patterns, including education and labor characteristics. In terms of land and housing, in all three cities, almost half of the poor who reported being property owners have weak, or no documentation over their properties, and, considerable portions of the poor population, are not connected to the public aqueduct, while few if any, receive help from the government. High dependency on public transportation was reported, e.g., one hundred percent in El Salvador, ninety seven percent in Tegucigalpa. Institutional, and policy issues explain the current situation: in terms of decentralization, municipalities have limited functions vis-a-vis the delivery of basic services; as for the housing sector, there is a vast gap between housing provision, and housing finance; and, particularly for water, and sanitation, the institutional framework for the delivery of basic services, is characterized by great uncertainty. Strikingly, public transportation is entirely provided by the private sector, but the lack of regulation, causes problems reflected in an overall low quality of service.